Recent advances in amidyl radical-mediated photocatalytic direct intermolecular hydrogen atom transfer - Hao-Sen Wang; Lin Li; Xin Chen; Jian-Li Wu; Kai Sun; Xiao-Lan Chen; Ling-Bo Qu; Bing Yu (Beilstein Journal of Organic Chemistry)
In recent years, amidyl radicals have emerged as highly efficient and versatile reagents for hydrogen atom transfer (HAT) in photocatalytic reactions. These radicals display exceptional selectivity and efficiency in abstracting hydrogen atoms from C–H, Si–H, B–H, and Ge–H, positioning them as invaluable tools in synthetic chemistry. This review summarizes the latest advancements in the photocatalyzed generation of amidyl radicals as HAT reagents, with a particular emphasis on their role in the intermolecular HAT process. We highlight key developments, mechanistic insights, and emerging strategies that harness the unique reactivity of amidyl radicals in the selective functionalization of a variety of substrates.